Prevalence of rotavirus infection among children with acute diarrhoea after rotavirus vaccine introduction in Kenya, a hospital cross-sectional study - Catherine Muendo; Ahmed Laving; Rashmi Kumar; Boniface Osano; Thaddaeus Egondi; Pamela Njuguna (BMC, 2018)
Abstract Background Rotavirus infection is the most common cause of acute gastroenteritis globally in children under 5 years of age and is responsible for approximately 5% of all child deaths yearly. Rotavirus vaccination is considered an effective public health strategy to prevent infection and reduce the severity of disease. Multi-centre country trials on rotavirus vaccines demonstrated efficacy rates of more than 85% in developed countries but only about 65% in developing nations. Rotavirus vaccination was introduced into the Kenya Expanded Programme on Immunization (KEPI) in 2014. The objective of our study was to determine the prevalence of rotavirus infection, severity of acute diarrhoea and to determine the rotavirus vaccination status among children aged 3-24 months presenting with acute diarrhoea at Kenyatta National Hospital after introduction of rotavirus vaccine in Kenya. Methods A total of 365 children aged 3-24 months presenting with acute diarrhoea at KNH were recruited from August 2016 to April 2017. Data on rotavirus vaccination status, nutritional status, feeding practices and sociodemographic characteristics were obtained and a full clinical evaluation of the patients was done. Severity of the gastroenteritis was assessed using the 20 point Vesikari Clinical Severity Scoring System. The children who were admitted were followed up for 7 days using hospital ward registers. Comorbid conditions were established from patient's clinical records and physical examination. Stool specimens from study participants were tested for rotavirus using a commercially available enzyme linked immunosorbent immunoassay kit- ProSpecT Rotavirus Microplate Assay. Results Majority of the children (96.7%) had received rotavirus vaccinations. The overall rotavirus prevalence was 14.5% and was higher among 17-24 months at 19.5%. The prevalence somewhat differed by gender, nutritional status, exclusive breastfeeding status, age and education level of mother/caregiver. Overall, a half of the children had severe acute diarrhoea and there were some differences in severity by child/mother characteristics. Conclusion There is still burden of rotavirus diarrhoea after introduction of rotavirus vaccine and the prevalence varies by child characteristics.